2021
DOI: 10.1016/j.heliyon.2021.e07737
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine versus propofol administration on the attenuation of hemodynamic responses during extubation in the adult elective surgical patient: A prospective cohort

Abstract: Background Tracheal extubation is the process of removing a tube from the trachea. It is associated with an increase in heart rate, blood pressure, intracranial pressure, intraocular pressure, coughing, bronchospasm, laryngospasm, and bleeding. Many techniques, as well as drugs, have been attempted for attenuation of the airway and cardiovascular responses. Propofol and lidocaine are widely available drugs in resource-limited settings even though their relative effectiveness for smooth extubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Data are expressed as median + up-interquartile range/down up-interquartile range. *** P < 0.001 vs. group C; # # P < 0.01, ### P < 0.001 vs. group F, respectively myocardial ischaemia, and intracranial pressure elevation [17][18][19].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Data are expressed as median + up-interquartile range/down up-interquartile range. *** P < 0.001 vs. group C; # # P < 0.01, ### P < 0.001 vs. group F, respectively myocardial ischaemia, and intracranial pressure elevation [17][18][19].…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, it is very important to prevent coughing caused by the endotracheal tube. The endotracheal tube-induced airway response (especially during intubation and extubation) also increases the risk of adverse cardiovascular events, including arrhythmias, hypertension, myocardial ischaemia, and intracranial pressure elevation [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it also inhibits the release of adrenaline and catecholamine and alleviates the stress response caused by a surgical operation. [ 11 , 12 ] Studies have shown that intravenous application of 1.5 mg/kg lidocaine reduces hemodynamic changes during endotracheal intubation, extubation, and operation. [ 13 ] Our results showed that MAP decreased at T1 in both groups; however, it was significantly decreased in group L but not in group C. HR decreased at T1 in group L. These results indicate that low-dose lidocaine reduces the stress response caused by endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is very important to prevent the choking reaction caused by the endotracheal tube. Furthermore, the endotracheal tube induced airway response (especially during endotracheal intubation and extubation) is prone to increase the risk of adverse cardiovascular events including arrhythmias, hypertension, myocardial ischemia, and intracranial pressure elevation [17][18][19]. During the recovery period of general anesthesia, sputum aspiration and tracheal tube extraction are the strongest stimulation to tracheal mucosa and most likely to induce cough reaction.…”
Section: Discussionmentioning
confidence: 99%